Dialogue systems with audio context - Young, Tom (2022)
Research on building dialogue systems that converse with humans naturally has recently attracted a lot of attention. Most work on this area assumes text-based conversation, where the user message is modeled as a sequence of words in a vocabulary. Real-world human conversation, in contrast, involves other modalities, such as voice, facial expression and body language, which can influence the conversation significantly in certain scenarios. In this work, we explore the impact of incorporating the audio features of the user message into generative dialogue systems. Specifically, we first design an auxiliary response retrieval task for audio representation learning. Then, we use word-level modality fusion to incorporate the audio features as additional context to our main generative model. Experiments show that our audio-augmented model outperforms the audio-free counterpart on perplexity, response diversity and human evaluation.